Peran Aktif Wanita pada Ekonomi dan Politik di Kalimantan Utara - Yustie, Renta; Hariani, Ermatry; Widyawati, Retno Febriyastuti; Putri, Ferdhea Amalia; Firmansyah, Mochammad Fikri; Ramadhani, Novira Eka (OECONOMICUS Journal of Economics, 2024)
Gender is one of the important issues and main discussions in North Kalimantan Province. The existence of gender issues is marked by the contribution of women's active role in the economic and political sectors in North Kalimantan which is still relatively low with a gender empowerment index in the range of 50 to 60 percent. Focusing on the role and function of women in society and government in their contribution to the regional economy and politics in North Kalimantan Province, it is necessary to increase the active role of women. The active role and function of women are measured by 3 (three) factors, namely the Women's Labor Force Participation Rate (TPAK), the involvement of women in parliament, and women's income contributions so that these three factors are independent variables in the study that will affect gender empowerment which is used as a dependent variable in the study. Developing and balanced gender empowerment can increase the role and position of women's workers in society formally and encourage sustainable development in North Kalimantan Province. This study is a quantitative study with secondary data sourced from the BPS of North Kalimantan Province. The research sample used 5 districts / cities in North Kalimantan Province, namely Malinau Regency, Bulungan Regency, Tana Tidung Regency, Nunukan Regency, Tarakan City. The research method uses a panel method with a period of 2018 to 2022, with a multiple linear regression model of panel data. The alpha value (α) in the study is 5% or equivalent to 0.05 and the results are expected that all independent variables in the study are able to influence the dependent variable, namely the gender empowerment index to increase the active role of women for the position of female workers in the economic and political sectors that are able to encourage sustainable development in North Kalimantan Province in the long term and support SDG's at point 5, namely gender equality. The purpose of this study is to test and analyze the factors that influence the active role of women in the economic and political sectors in North Kalimantan